2003
DOI: 10.1515/zna-2003-1206
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Ferrofluid Drops

Abstract: We study the stationary shapes and the rotational motion of drops of magnetic fluids floating in a non-magnetic liquid of equal density and spun up by an externally applied rotating magnetic field. For a sufficiently large magnetic susceptibility of the drop fluid transitions to non axial-symmetric shapes take place when the field amplitude is increased. We give a detailed theoretical account of the character of these shape bifurcations, of the resulting stationary drop forms, and of the slow rotational motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Taking into account the various contributions two equations for Ω and ζ can be derived. The final expressions are rather long and will be published elsewhere [22]. Results for the rotation frequency Ω of the drop are shown in fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the various contributions two equations for Ω and ζ can be derived. The final expressions are rather long and will be published elsewhere [22]. Results for the rotation frequency Ω of the drop are shown in fig.…”
mentioning
confidence: 99%
“…The remaining differences with the experiment may be due to the magnetic particle size polydispersity of the fluid resulting in a whole spectrum of relaxation times, and a small ellipticity of the external field. These questions will be dealt with in detail elsewhere [23].…”
mentioning
confidence: 99%
“…The penetrant may be applied to all non-ferrous materials and ferrous materials, but for inspection of ferrous components magnetic-particle inspection is also preferred for its subsurface detection capability. The experiments presented above in full generality are a formidable task [4]. The impact of the magnetic field on the ferrofluids drop is described by the magnetic stress Where B, H and M denote the magnetic induction, the magnetic field and the magnetization respectively.…”
Section: Sensor and Data Collectionmentioning
confidence: 99%
“…However, it should be fulfilled on average. It can be shown that this requirement is equivalent to the energy dissipation balance in the system stating that per time unit the energy fed into the system by the magnetic field must be equal to the energy dissipated in the viscous flows and the periodic re-magnetization of the ferrofluid [23].…”
Section: 10mentioning
confidence: 99%
“…Naturally this makes the theoretical analysis more complicated and less accessible to analytical techniques. A detailed theoretical discussion of the implications of a non-linear magnetization law on the problem at hand can be found in [23]. Here we will only mention the main points and present some of the results which can be obtained by using the complete magnetization function M = M(H ) as determined in an independent experiment.…”
Section: Non-linear Magnetization Lawmentioning
confidence: 99%